Position of The Will Deed That is not in Accordance with Article 902 of The Civil Code on The Inheritance of The Second Marriage - Putri Hairani; Liza Priandhini (IHSA Institute, 2022)
A will is the will of the testator that contains the wishes of the testator as long as it is permitted by law and must be used as a basis for carrying out the division of the property he inherits. That the testator in the making of the will often deviates from the provisions contained in the statute, but for heirs in a straight line upwards or downwards cannot be excluded and harmed because they are guaranteed by the existence of an absolute share or legitieme portie which can be prosecuted if his absolute share is violated. And besides that in the will there are restrictions / prohibitions that must be met in its implementation. This study analyzes the decision of the Jakarta High Court Number 246 / PDT / 2020 / PT DKI, regarding a rule regarding the position of the will deed given to the second wife who violates the restrictions / prohibitions that are not in accordance with the provisions of article 902 of the Civil Code, namely that there is an error in the application of the law in the inheritance of the heir. The dispute between the heirs caused the inheritance's estate to have not been divided and the will deed was annulled by a court decision. The annulment of the will deed by the court is incorrect. The research method used in this research is normative juridical research or literature law research with the form of analytical descriptive research. The author uses secondary data types to solve the subject matter that arises.